2010
DOI: 10.2174/1876214x01003010034
|View full text |Cite
|
Sign up to set email alerts
|

Manganese (II) Chloride-Catalyzed Conjugated Addition of Amines to Electron Deficient Alkenes in Methanol-Water Medium~!2009-10-16~!2009-12-15~!2010-03-30~!

Abstract: A simple, general and efficient method has been developed for the conjugate addition of a variety of aliphatic and aromatic amines to electron deficient alkenes in the presence of a catalytic amount of manganese (II) chloride in methanol-water to produce the corresponding-amino derivatives in excellent yields at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is also possible for amine groups of the 8-arm PEG to react with methacrylate groups of OMA by Michael addition reaction. However, since the Michael addition reaction rate is much slower (from hours to days) [27] when compared to the Schiff base reaction rate between amine and aldehyde groups and the photopolymerization, it likely occurs only to a minimal extent.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible for amine groups of the 8-arm PEG to react with methacrylate groups of OMA by Michael addition reaction. However, since the Michael addition reaction rate is much slower (from hours to days) [27] when compared to the Schiff base reaction rate between amine and aldehyde groups and the photopolymerization, it likely occurs only to a minimal extent.…”
Section: Resultsmentioning
confidence: 99%
“…In 2005, Yang et al [1] showed the ultrasound-assisted Michael addition of amines with ferrocenium under solvent-free condition at room temperature. Phenolate-catalysed aza-and thio-Michael addition in aqueous media were reported by Tamami and co-workers [2] with polymer supported Mn(II)-catalysed addition of amines with alkenes in methanol water medium, report is available in the literature [3]. Microwave-irradiated addition of amines to methyl acylates was reported in the year 2008 [4].…”
Section: Introductionmentioning
confidence: 99%
“…There are very few mentions of Mn(II) as Lewis acid catalyst in the literature (Horike et al 2008;Roy et al 2010). Mn(II) salts are usually described as weak Lewis acids, which may explain their almost absence in the field of Lewis acid catalysis (Cahiez et al 2001b).…”
Section: Resultsmentioning
confidence: 99%